Comment vraiment écouter (Assemble You, 2022)
Welcome to Assemble You Audio Learning. How many times have you been made uncomfortable by a conversation in which you are heard but not really listened to? Besides, be honest, you have most certainly happened more than once to be that person who did not really listen to what your interlocutor was telling you. Poor listening leads to mistakes and misunderstandings, which can, in turn, lead to ineffective decisions and costly business mistakes. When an executive doesn't listen to people he's hired himself, he may be missing out on suggestions that have immense potential. On a more personal level, poor listening quality can hurt and lead to a loss of cohesion within the team. In this module, we will show you concrete techniques to transform your listening skills. Learning Objectives To be aware of the disadvantages of not listening to others and to realize that the average person does not listen effectively To learn tips and tricks to improve your listening skills in a significative way.